The Duterte Administration's Foreign Policy: Unravelling the Aquino Administration's Balancing Agenda on an Emergent China - Renato Cruz De Castro (Journal of Current Southeast Asian Affairs, 2016)
From 2010 to 2016, then-President Benigno Aquino balanced China's expansive maritime claim in the South China Sea. President Aquino challenged China by shifting the AFP's focus from domestic security to territorial defence, bolstering closer Philippine–US security relations, acquiring American military equipment, seeking from Washington an explicit security guarantee under the 1951 Mutual Defence Treaty (MDT), and promoting a strategic partnership with Japan. However, the Duterte administration is unravelling its predecessor's balancing agenda by distancing itself from the United States and gravitating closer to China, despite the Permanent Court of Arbitration (PCA) July 12 2016 award to the Philippines. President Duterte's foreign policy is directed at reviving the equi-balancing policy on China, in contrast to then-President Aquino's balancing strategy. This is best exemplified by his efforts to harness China for several major infrastructure and investments projects in the Philippines and to resort to bilateral negotiations with Beijing. The present article argues that instead of relying on the US, President Duterte is fostering closer security partnership with Japan to equi-balance an emergent China.